Determinants of Stock Price Volatility in Nepalese Enterprises - Budhathoki, Subas (Nepalese Journal of Finance, 2024)
The study examines the determinants of stock price volatility in Nepalese enterprises. Coefficient of variation of market price per share and market capitalization are selected as dependent variables. The selected independent variables are interest rate, inflation rate, gross domestic product, money supply, financial leverage, company size and earnings per share. The study is based on secondary data of 5 commercial banks, development bank and manufacturing companies with 120 observations for the study period from 2015/16 to 2022/23. The data were collected from the annual reports of the respective companies, annual report of Nepal Rastra Bank (NRB) and the website of Merolagani. The correlation coefficients and regression models are estimated to test the significance and importance of firm specific and macroeconomic factors on the stock price volatility in Nepalese enterprises. The study showed that interest rate has a negative effect on coefficient of variation of market price per share (CVMPS) and market capitalization (MCAP). It means that increase in interest rate leads to decrease in CVMPS and MCAP. Similarly, earnings per share have a negative effect on CVMPS and MCAP. It indicates that increase in earnings per share leads to decrease in CVMPS and MCAP. However, money supply has a positive impact on CVMPS and MCAP. Moreover, leverage has a negative effect on CVMPS and MCAP. It indicates that increase in leverage leads to decrease in CVMPS and MCAP. However, money supply has a positive impact on CVMPS and MCAP. It means that higher the money supply, higher would be the CVMPS and MCAP. In contrast, gross domestic product has a negative impact on CVMPS. It shows that larger the gross domestic product, lower would be the CVMPS. Moreover, company size has a positive impact on MCAP. It means that larger the company size, higher would be the MCAP. Likewise, gross domestic product has a positive impact on MCAP. It indicates that larger the gross domestic product, larger would be the MCAP. In contrast, inflation rate has a negative impact on CVMPS. It shows that increase in inflation rate leads to decrease in CVMPS.